A contextual approach on the views of Muslim feminists interpreters of the Qur'an regarding women and their rights in the society - Ali, Md. Yousuf (2010)
The interpretation of the texts of the Qur’Én regarding the rights, role, and status of women is a challenge and much debatable subject. The Qur’Én is seen by almost all Muslims as the literal words of Allah (swt). The majority Muslim exegetes interpreted the verses of the Qur’Én by applying a method of literal reading. In modern context, regarding women’s rights, Muslim feminist interpreters of the Qur’Én have applied a contextual approach with regard to the historical, social, and political context in which the verses were revealed in order to disclose an underlying liberal intent, which may liberate Muslims from a literal reading of the Qur’Én. However, feminists face a particular challenge and accusation from traditional Muslim exegetes. The accusation is that feminist scholarship is not loyal to the teachings of Islam and its heritage, but produces liberal Islam and liberal Shar’ÊÑah, influenced by the Western values and imposed upon Islam. The article focuses on how the method of contextualization is applied to some contentious verses in the Qur’Én, which are related to the rights, role and status of women in Islam. These verses represent the arguments at which feminists face a great challenge. Two questions on the basis of those verses will be examined; one is the question of men’s authority over women and the other is woman’s leadership in modern context. For instances, the contentious verse 4:34 recognizes man’s authority and superiority over woman for certain tasks and the verse 9:71 also recognizes the sovereign power of women ‘al-WilÉyah al-Mutlaqah’ equally in participating nation-building. We examine how two contemporary feminists Muslim thinkers; Fatima Mernissi, a Moroccan sociologist and Aminah Wadud Muhsin, an African- American professor of Islamic Studies use the hermeneutical method of contextual reading to interpret the texts of the Qur’Én. The article evaluates the theoretical and practical challenges faced by them from traditional exegetes and argues that whether such a methodology strengthens their arguments and a fuller discussion of the issues that it raises regarding woman’s rights? It is also argued that through the interpretation of the contextualization one may find difference with the previous interpretation of the Qur’Én, which is central to feminists exegesis.